Front Cover. Issue 2 (18th January 2018) - Doña, Jorge; Proctor, Heather; Mironov, Sergey; Serrano, David; Jovani, Roger
Abstract : The cover image, by Jorge Doña et al., is based on the Research Paper Host specifi city, infrequent major host switching and the diversification of highly host‐specific symbionts: The case of vane‐dwelling feather mites, DOI:10.1111/geb.12680 . Colorized SEM Image Credit: Heather Proctor, University of Alberta.